Life - The Outburst of Life in the Human Sphere
XVI, 514 p.
Keywords: Science and philosophy have both undergone radical transformations in recent times. Now they are poised for a pivotal alliance. Science has abandoned the mechanistic model of nature. Philosophy has broken through the tight, traditional circle of conceptualisation, intellectualistic preconceptions and cognitive presuppositions. The two now meet to focus on the palpitating, fluctuating stream of nature/life. Their traditional prejudices dispersed under the pressure of new evidence, philosophy/phenomenology of life and the sciences of life meet in the Archimedean point of the human creative condition (proper to the phenomenology of life) and the role of the human subject (central to the scientific view of reality). They necessitate each other: without the sciences of life, philosophy/phenomenology of life cannot penetrate the intricacies of nature/life; without recourse to philosophy to delineate, design, provide clues to the organisation of natural evidence, the sciences of life cannot devise new strategies for inquiry nor survey their field. The present collection throws open the barriers that separate nature and culture, works of physis and those of the spirit. Following the philosophical model of the ontopoieisis of life, focusing on its specifically human sphere - that of the human self-interpretation-in-existence - it encircles the vast, new horizons of the new alliance.